Efecto de la alimentación con sangre humana sobre la fecundidad, fertilidad y ciclo biológico de Rhodnius prolixus (Hemiptera: Reduviidae) - Aldana, E; Lizano, E; Valderrama, A (Revista de Biología Tropical, 2001)
The effect of several human blood fractions artificially fed to Rhodnius prolixus Stal 1859 on oviposture (fecundity), egg-hatching (fertility) and life cycle was observed. Specimens fed on man´s blood were more fecund than those fed with woman´s blood. There were no significant differences in fertility related to host sex. The nymphal development time and number of feedings to molt to the following instar were estimated. Animals fed only on blood plasm did not finish nymphal development, while those fed only blood red cells ended their life cycle in the third nymphal instar. Total life cycle lasts 129 days in individuals fed with whole blood.